Symposium 1: Research Underpinnings of the UK eUniversity - Bacsich, Paul; Mason, Robin; Slater, John (Proceedings of the International Conference on Networked Learning, 2002)
The UK eUniversity, run by the organisation whose full name is UKeUniversities worldwide, will start taking students in autumn of this year from all around the world, studying almost completely by remote e-learning. Already there are three fast-track pilot consortia developing material and around a dozen more in negotiation with the eUniversity, generating a conceptual "footprint" on over 40 universities already. The impact of the eUniversity on UK HE thinking on e-learning is likely to be as influential in the longer term as the setting up of the Open University was on distance learning. What is not yet well known is that behind the setting up of the eUniversity lies a comprehensive set of studies drawing on best practice in e-learning theory and practice, pedagogy and technology, at university level both in the UK and beyond. While some of this has become visible via the PriceWaterhouseCoopers study material made public by HEFCE, the annexes to these – and much more recent material – have not been released for reasons of commercial confidentiality until the key agreements were in place. Now much more information can be given and the theories (and proposed practice) exposed to dialogue with e-learning experts in the wider community. Apart from its intrinsic research interest, the eUniversity understands that pilots will have to internalise and adapt the information to their own situations, and to do this requires a deep understanding of the thinking, not just the surface recommendations. This symposium takes the form of a "Master Class" comprising presentations from three individuals who have been closely involved with the development of the eUniversity concept. A discussant will engage the presenters in dialogue and the session will conclude with a general discussion inviting contributions from the audience. Papers: Review of E-Learning for Education and Training Robin Mason An Innovative Model for eLearning Delivery: the United Kingdom eUniversity John Slater